Smoking Trends Among Adolescents in One Region of Korea - Park, Min-Hee (Advances in Social Sciences Research Journal, 2022)
This descriptive study examined the smoking status of adolescents in one region of South Korea. Data collection for this study was conducted online in 2021, under the supervision of the local education office. The survey participants were 28,256 students aged between 11 and 18 years. In this study, the smoking experience rate was 4.2%, the current smoking rate was 1.7%, and daily smoking rate was 0.9%. A comparison by school showed a high trend in specialized vocational high schools. In addition, compared with 2020, the overall smoking rate among adolescents showed a decreasing trend. In addition, the smoking experience rate, current smoking rate, and daily smoking rate in 2021 compared with 2016 showed a tendency to decrease overall. It is necessary to continuously implement and expand smoking prevention programs aimed at reducing smoking rates among adolescents and students.